Brief Report: Integrase Strand Transfer Inhibitors Are Associated With Lower Risk of Incident Cardiovascular Disease in People Living With HIV. (1st August 2020) - O'Halloran, Jane A.; Sahrmann, John; Butler, Anne M.; Olsen, Margaret A.; Powderly, William G.
Abstract : Background: Several antiretroviral therapy (ART) classes have been associated with increased myocardial infarction (MI) risk. Cardiovascular disease in people living with HIV (PLWH) on integrase strand transfer inhibitors (INSTI) has not been examined. Here we aim to examine this. Setting: Retrospective cohort design study. Methods: We used the IBMMarketScan databases for U.S. commercially insured and Medicaid covered adults to identify PLWH newly initiated on ART between January 1, 2008 and December 30, 2015. Major adverse cardiac event (MACE), a composite of acute MI, ischemic stroke, coronary artery bypass grafting, and percutaneous coronary intervention was the primary outcome. We used calendar time-specific probability-weighted Cox proportional hazards models to estimate hazard ratios and 95% confidence intervals for the association between INSTI use and MACE. We used propensity score weighting methods to account for potential confounding. Results: Twenty thousand two hundred forty-two new ART initiators were identified. 5069 (25%) PLWH initiated INSTI-based regimens. 203 MACE events occurred; acute MI 16 (0.32%) vs 66 (0.43%), stroke 24 (0.47%) vs 54 (0.36), coronary artery bypass grafting 2 (0.04%) vs 9 (0.06%), percutaneous coronary intervention 7 (0.14%) vs 25 (0.16%) of INSTI users vs non-users. INSTI-based ART was associated with significantly lower risk of MACE events (hazard ratios 0.79; 95% confidence intervals: 0.64 to 0.96) compared with non–INSTI-based regimens. Conclusion: In this cohort, INSTI-based regimens were associated with a 21% decreased risk of incident cardiovascular disease. These finding require validation in other cohorts and with longer follow-up. Abstract : Supplemental Digital Content is Available in the Text.